(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
The historical discord between Eastern and Western civilizations traces its origins to ancient conflicts, notably the Medean wars between Greece and Persia. With the advent of Islam, religious dynamics further intensified these geopolitical tensions, culminating in pervasive Islamophobic sentiments. Though modern in nomenclature, the roots of Islamophobia in Europe can be traced back to the initial settlements of Muslims, particularly under the shadow of the Ottoman Empire. This fear was significantly fueled by the incendiary rhetoric of kings and emperors from major European powers, who sought to diminish the Islamic presence on the continent. This study focuses on the purported will of Peter the Great as a pivotal case study to explore its influence on Islam-West relations. Our investigation addresses four key areas: firstly, an examination of Peter the Great’s policies towards the Islamic Caliphate; secondly, the underlying motives behind his will; thirdly, the adherence of subsequent Russian emperors to this will; and fourthly, the relevance of Peter the Great’s directives in contemporary Russian politics. Through analytical comparison of historical documents and subsequent policies, we ascertain that Peter the Great’s directives were primarily strategic, aimed at positioning Russia as a dominant force in Europe. The religious façade he employed effectively mobilized Ottoman Christian populations against the Islamic Caliphate. Following his legacy, Russian leaders continued to employ strident anti-Muslim rhetoric, which not only diminished Ottoman territories but also solidified Islamophobia, a phenomenon that continues to cause profound distress among Muslim communities in regions like Bosnia and Herzegovina and Armenia.